Metode Drill dalam Pembelajaran Retorika Mahasiswa Program Studi Tadris Bahasa Indonesia IAIN Madura - Jinan, Roihal (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
One method that lecturers can apply to improve students' communication skills is the drill method. The drill method is a practical exercise that must be done repeatedly by students to gain knowledge and public speaking skills so that a person's speech becomes less rigid, fluent and structured. This research is included in qualitative descriptive research with research subjects, namely Indonesian Tadris students. To collect data, researchers used observation and documentation guidelines. The process of implementing the drill method in the rhetorical abilities of students in the Indonesian Tadris Study Program at IAIN Madura has gone well. This method is applied in stages 1) goal setting, 2) explanation of instructions, 3) precision, 4) practice, 5) evaluation, and 6) repetition. The application of the training method to Indonesian Language Tadris students at IAIN Madura is very good, not only improving speaking skills, but also increasing students' confidence in speaking in public in various communication contexts.